Variations in biomarkers of dyslipidemia and dysbiosis during the menstrual cycle: a pilot study in healthy volunteers - Helena Bergström; Lena Ekström; Anna Warnqvist; Peter Bergman; Linda Björkhem-Bergman (BMC, 2021)
Abstract Background Dyslipidemia in metabolic syndrome may introduce an underestimation of the risk for cardiovascular disease (CVD) using Low-Density Lipoprotein-Cholesterol (LDL-C) as a surrogate marker. Recently, non-High-Density Lipoprotein-Cholesterol (non-HDL-C), Apolipoprotein B (ApoB) and remnant-Cholesterol (remnant-C) have been suggested as better biomarkers for dyslipidemia. In addition, the microbial metabolites trimethylamine-N-oxide (TMAO), betaine and choline have been associated with CVD and suggested as markers for dysbiosis. There is a lack of knowledge on potential alterations in these biomarkers during the menstrual cycle. The aim of this single center, prospective non-interventional study, was to investigate variations in biomarkers of dyslipidemia and dysbiosis in healthy volunteers during the menstrual cycle. Method Serum samples were collected from 17 healthy, regularly menstruating women during two menstrual cycles, including the follicular, ovulatory and luteal phases. Levels of lipoproteins, lipoprotein ratios and microbial metabolites were analyzed in a total of 90 samples (30 complete menstrual cycles). Results ApoB, ApoB/HDL and non-HDL-C/HDL ratios were significantly higher in the follicular phase compared to the ovulatory and luteal phases (p < 0.05). Remnant-C were higher during the luteal phase (p < 0.05). TMAO did not vary during the different phases and did not correlate with estrogen levels. Conclusion Our data support that biomarkers for dyslipidemia vary during the menstrual cycle. Thus, to avoid an underestimation of cardiovascular risk, sampling during the follicular phase, when levels of pro-atherogenic lipids are higher, may be considered.